On the method, genre and style of Vaižgantas' "Pragiedruliai" - Algimantas Radzevičius (Literatūra (Vilnius))
The article deals with Vaižgantas' "Pragiedruliai" (part 1 - 1918, part 2 - 1920) with respect to the synthetic artistic method that is typical of the writer. The synthetic artistic method is understood here as a synthesis of contradicting and opposite artistic principles and devices, as a phenomenon inherent both in the literary traditions and in the dialectics of the consciousness of the author himself. These premises taken as a basis, the article is an attempt to discuss such questions of the genre, style and methods of Vaižgantas' work that have not been given proper attention as yet.